The Transdisciplinary Approach: A Critical Appraisal from an “Islamic Perspective” (American Journal of Islam and Society, 2015)
This paper argues that the transdisciplinary approach, contrary to the views of some of its advocates, is not a methodology but a metamethod. In the first part I shall briefly discuss the similarities and differences between science/knowledge and technology to explain important epistemic implications of placing this approach in the latter category. Next, I shall critically examine the views of Basarab Nicolescu, one of the most prolific proponents of a particular reading of this approach. Part three discusses the function of the transdisciplinary approach as a meta-method. In the fourth and final part I shall try to introduce some examples from the intellectual econiche of Islamic culture in a bid to shed further light on this approach’s potential as a meta-method. The conclusion, which I draw from my own critical examination, is that the transdisciplinary approach can be used in an effective way, provided that its users adopt an appropriate philosophical framework. Such a framework, I contend, could be provided by critical rationalism.